PENDAMPINGAN MASYARAKAT DESA HUTAN (BINAAN PT. WWI) DALAM PENERAPAN METODE PENGUKURAN CADANGAN KARBON DI DESA WAPSALIT KABUPATEN BURU - Mustamu, Sofia; Hatulesila, Jan W.; Mardiatmoko, Gun (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2024)
Carbon reserves in forests play a crucial role in climate change mitigation and the preservation of global ecosystems. Forests act as primary absorbers of carbon dioxide (CO2) from the atmosphere, storing carbon in the biomass of trees, soil, and leaf litter. This community service aims to provide understanding and education to the public about carbon storage, factors influencing storage capacity, and the implications of sustainable forest management. The methodology used includes direct measurement of carbon reserves in various forest types and the analysis of secondary data from scientific literature. Survey results indicate that the village forest of Wapkalit still has significant potential, emphasizing the need for community awareness to continue managing and preserving the forest. Socialization conducted through the FGD (Focus Group Discussion) method can directly impart knowledge to the community.